Resection of Hepatic Colorectal Metastases Involving the Caudate Lobe - Abdalla, Eddie (2007)
Purpose: To examine clinical features and outcome of patients who underwent hepatic resection for colorectal liver metastases (LM) involving the caudate lobe. Patients and Methods: Consecutive patients who underwent hepatic resection for LM from May 1990 to September 2004 were analyzed from a multicenter database. Demographics, operative data, pathologic margin status, recurrence, and survival were analyzed. Results: Of 580 patients, 40 (7%) had LM involving the caudate. Six had isolated caudate LM and 34 had LM involving the caudate plus one or more other hepatic segments. Patients with caudate LM were more likely to have synchronous primary colorectal cancer (63% vs. 36%; P = 0.01), multiple LM (70% vs. 51%; P = 0.02) and required extended hepatic resection more often than patients with non-caudate LM (60% vs. 18%; P < 0.001). Only four patients with caudate LM underwent a vascular resection; three at first operation, one after recurrence of a resected caudate tumor. All had primary repair (vena cava, n = 3; portal vein, n = 1). Perioperative complications (43% vs. 28%) and 60-day operative mortality (0% vs. 1%) were similar (caudate vs. non-caudate LM, both P > 0.05). Pathological margins were positive in 15 (38%) patients with caudate LM and in 43 (8%) with non-caudate LM (P < 0.001). At a median follow-up of 40 months, 25 (64%) patients with caudate LM recurred compared with 219 (40%) patients with non-caudate LM (P = 0.01). Patients with caudate LM were more likely to have intrahepatic disease as a component of recurrence (caudate: 51% vs. non-caudate: 25%; P = 0.001). No patient recurred on the vena cava or portal vein. Patients with caudate LM had shorter 5-year disease-free and overall survival than patients with non-caudate LM (disease-free: 24% vs. 44%; P = 0.02; overall: 41% vs. 58%; P = 0.02). Conclusions: Patients who undergo hepatic resection for caudate LM often present with multiple hepatic tumors and tumors in proximity to the major hepatic veins. Extended hepatectomy is required in the majority, although vascular resection is not frequently necessary; when performed, primary repair is usually possible. Despite resection in this population of patients with multiple and bilateral tumors, and despite close-margin and positive-margin resection in a significant proportion, recurrence on the portal vein or vena cava was not observed, and long-term survival is accomplished (41% 5-year overall survival).